2011
DOI: 10.1016/j.ejmech.2011.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Novel pentamidine derivatives: Synthesis, anti-tumor properties and polynucleotide-binding activities

Abstract: Novel amidino substituted conformationally restricted derivatives of pentamidine were synthesized and their antiproliferative activity against several human cancer cell lines determinated. It was found that introduction of furandicarboxamide core moiety (9, 10) increases antiproliferative activity as well as selectivity against certain tumor cell lines in comparison with amidino-substituted furan-mono-carboxamide (5, 6). Unlike the furan series where iso-propyl substituted amidine (10) exhibits more potent ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 29 publications
(34 reference statements)
0
13
0
Order By: Relevance
“…Several pentamidine derivatives have antiproliferative activity against several human cancer cell lines 2,3. However, these exhibit a number of serious side effects, toxicity problems, and poor availability 4.…”
Section: Introductionmentioning
confidence: 99%
“…Several pentamidine derivatives have antiproliferative activity against several human cancer cell lines 2,3. However, these exhibit a number of serious side effects, toxicity problems, and poor availability 4.…”
Section: Introductionmentioning
confidence: 99%
“…Amidino-substituted conformationally restricted derivatives of pentamidine were synthesized (Scheme 27) [68]. It was found that introduction of furandicarboxamide core moiety (97, 98) antiproliferative activity as well as selectivity against certain tumor cell lines in comparison with amidino-substituted furan-mono car-boxamide.…”
Section: Cnmentioning
confidence: 99%
“…For background and the biological activity of aromatic amidines, see: Chen et al (2010); Hu et al (2009); Del Poeta et al (1998); Baraldi et al (2004); Jarak et al (2011); Neidle (2001); Stolić et al (2011). For the synthesis, see Widra et al (1990).…”
Section: Related Literaturementioning
confidence: 99%